Unit group of integral group ring ℤ(G × C3) - Ömer Küsmüş (Miskolc Mathematical Notes)
Presenting an explicit descryption of unit group in the integral group ring of a given non-abelian group is a classical and open problem. Let S3C3ℤ(S3×C3)(F55⋊F3)⋊(S3∗×C2)Fρρℤ(S3×C3)S3RS3R=ℤ[ω]ωℤ(G×C3)GV(G)GU(ℤ(G×C3))